Analysis of the Novel Fanconi Anemia Gene SLX4/FANCP in Familial Breast Cancer Cases. Issue 1 (11th October 2012) - Bakker, Janine L.; van Mil, Saskia E.; Crossan, Gerry; Sabbaghian, Nelly; De Leeneer, Kim; Poppe, Bruce; Adank, Muriel; Gille, Hans; Verheul, Henk; Meijers‐Heijboer, Hanne; de Winter, Johan P.; Claes, Kathleen; et al.
ABSTRACT SLX4/FANCP is a recently discovered novel disease gene for Fanconi anemia (FA), a rare recessive disorder characterized by chromosomal instability and increased cancer susceptibility. Three of the 15 FA genes are breast cancer susceptibility genes in heterozygous mutation carriers—BRCA2, PALB2, and BRIP1. To investigate if defects in SLX4 also predispose to breast cancer, the gene was sequenced in a cohort of 729 BRCA1/BRCA2‐negative familial breast cancer cases. We identified a single splice site mutation (c.2013+2T>A), which causes a frameshift by skipping of exon 8. We also identified 39 missense variants, four of which were selected for functional testing in a Mitomycin C‐induced growth inhibition assay, and appeared indistinguishable from wild type. Although this is the first study that describes a truncating SLX4 mutation in breast cancer patients, our data indicate that germline mutations in SLX4 are very rare and are unlikely to make a significant contribution to familial breast cancer.